Wind‐driven nutrient pulses to the subsurface chlorophyll maximum in seasonally stratified shelf seas. Issue 20 (28th October 2013) - Williams, Charlotte; Sharples, Jonathan; Mahaffey, Claire; Rippeth, Tom
Abstract [1] Shelf seas are an important global carbon sink. In the seasonal thermocline, the subsurface chlorophyll maximum (SCM) supports almost half of summer shelf production. Using observations from the seasonally stratified Celtic Sea (June 2010), we identify wind‐driven inertial oscillations as a mechanism for supplying the SCM with the nitrate needed for phytoplankton growth and carbon fixation. Analysis of wind, currents, and turbulent dissipation indicates that inertial oscillations are triggered by a change in the wind velocity. High magnitude, short‐lived dissipation spikes occur when the shear and wind vectors align, increasing the daily nitrate flux to the SCM by a factor of at least 17. However, it is likely that the sampling resolution of turbulent dissipation does not always capture the maximum wind‐driven peak in mixing. We estimate that wind‐driven inertial oscillations supply the SCM with ~33% to 71% of the nitrate required for new production in shelf seas during summer.